2021
DOI: 10.1177/00031348211058639
|View full text |Cite
|
Sign up to set email alerts
|

Bronchoscopy Decreases Ventilator-Associated Pneumonia in Trauma Patients

Abstract: Health care-associated pneumonias (HAPs) are a significant comorbidity seen in hospitalized patients. Traumatic injury is a known independent risk factor for the development of HAP. Trauma-related injuries also contribute to an increase in the rate of pneumonia in mechanically ventilated patients requiring intensive care unit (ICU) treatment. In 2011, the ventilator-associated pneumonia (VAP) rate among ICU patients at our institution (CMMC) increased dramatically. As a result, our infection control specialist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Mirtalaei et al 6 found that prophylactic pipercillin-tazobactam decreased early-onset VAP in intubated patient. Another study by Nannapaneni et al 25 found that patients intubated in the prehospital setting were less likely to develop VAP if they underwent BAL within 24 hours. Thakkar et al 8 found that early antibiotic prophylaxis altered the antibiotic flora of subsequent VAP in intubated trauma patients.…”
Section: Discussionmentioning
confidence: 99%
“…Mirtalaei et al 6 found that prophylactic pipercillin-tazobactam decreased early-onset VAP in intubated patient. Another study by Nannapaneni et al 25 found that patients intubated in the prehospital setting were less likely to develop VAP if they underwent BAL within 24 hours. Thakkar et al 8 found that early antibiotic prophylaxis altered the antibiotic flora of subsequent VAP in intubated trauma patients.…”
Section: Discussionmentioning
confidence: 99%
“…Few previous studies have investigated the prognostic effects of bronchoscopy among patients with VAP, with many studying the value of bronchoscopy for diagnosing or preventing VAP ( Timsit et al, 2001 ), or limited to specific populations such as trauma or pediatric patients ( Bush, 2003 ; Nannapaneni et al, 2021 ). The present study included patients with VAP from the large public MIMIC-IV database as the study population.…”
Section: Discussionmentioning
confidence: 99%